Gas gangrene A surgical emergency - Part 1 - Aboud, Diane; Williams, Jan (Operating Room Nurses Association of Canada Journal, 1991)
Gas gangrene is caused by a local infection with anaerobic, spore forming, gram positive Clostridium perﬁingens or Clostridium septicium. It is masked by the presence of gas in the soft tissues. Because gas gangrene is a lethal process, it is imperative that the muscle necrosis be recognized quickly and that the appropriate treatment be initiated immediately. This “Clostridium myonecrosis,” as it is called, is a rapidly progressive medical-surgical emergency.